Prebiotic Effect of Cogon Grass Root Extract on Stimulating Lactic Acid Bacteria Growth in Mice Intestine - Pradini, Gita W; Fauziah, Nisa; Asarina, Shinta; Anggareni, Neni; Widyastuti, Rini; Syamsunarno, Mas Rizky AA (Universitas Kristen Maranatha, 2024)
Lactic acid bacteria (LAB) are known for their numerous beneficial effects for health and their colonization within intestines is affected by prebiotic consumption. Cogon grass root is an herbal medicine which contain substantial quantities of polyphenols. Recently, many studies suggested polyphenols as a novel group of prebiotics. Therefore, this study aimed to explore prebiotic effect of cogon grass root extract (CGRE) on stimulating growth of LAB in mice intestine. Mice (n =7/group) were divided into three groups; group A (control), group B and C received CGRE orally with daily dosage 90 and 115mg/kg BW, respectively. After 14 days of treatment, all mice were sacrificed. LAB was isolated and counted from ileum. Additional biochemical tests were performed to confirm the bacteria as LAB. Further identification of representatives LAB was performed with API-CHL-50 System. We found increased growth and diversity of LAB in the treatment group with optimum growth stimulation at CGRE dosage 90mg/KgBW daily (group B). Further identification showed Lactococcus lactis was the most frequent LAB found in all groups, with additional Lactobacillus paracasei and Lactobacillus curvatus were found in the treatment group. These findings support additional benefit of CGRE as prebiotics by stimulating LAB growth and diversity in mice intestine.